Bertahan dan Berkembang : Strategi 3 Pilar Sukses KWT Puspa Gemari di Era Digital - Rosita Rosita; Dessy Isfianadewi; Dekar Urumsah; Reni Yendrawati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Women Farmers Group (KWT) has a strategic role in women's economic empowerment and agricultural-based product development. However, KWT Puspa Gemari in Bantul, Yogyakarta, still faces obstacles in calculating production costs, unattractive packaging design, and limited marketing. This community service initiative aims to enhance the sustainability of herbal medicine businesses through training on production cost analysis, packaging design, and digital marketing. Methods include observation, training, Focus Group Discussion (FGD), and mentoring. Results show improved member understanding of product costing (from 5 to 12 members), upgraded packaging (from plastic bottles to glass bottles with professional labels), and expanded marketing via digital platform with a Purchasing Order (PO) system. Significant impacts include production efficiency, product competitiveness, and market expansion. These activities demonstrate that an integrated approach to production management and digital marketing can strengthen the sustainability of women-led micro-businesses. Future recommendations include continuous mentoring, product diversification, and digital technology optimization to enhance KWT's market position.